Smart waste management system with IoT monitoring - Kalitazan, Sachein; Muniswaran, Suvarshan; Velan, Sheshan; Muniswaran, Suvathithan; Shah, Dhanesh (Universiti Teknologi MARA, Kedah, 2023)
The Smart Waste Management System (SWMS) with IoT monitoring is a cutting-edge solution that utilizes Internet of Things technologies to optimize waste management processes. By deploying smart waste bins with sensors and IoT devices, the system continuously monitors bin fill-levels, temperature, and other parameters, transmitting real-time data to a central monitoring platform. Through advanced data analytics and machine learning algorithms, the platform predicts waste accumulation patterns, optimizes collection routes, schedules pickups based on fill-level data, and detects any abnormal conditions. This IoT-based system ensures efficient waste collection, prevents overflows, reduces operational costs, promotes sustainability through waste segregation and recycling, and contributes toa cleaner and more sustainable environment.